Subcortical differentiation of stop consonants relates to reading and speech-in-noise perception - Hornickel, Jane (National Academy of Sciences, 2009)
Children with reading impairments have deficits in phonological awareness, phonemic categorization, speech-in-noise perception, and psychophysical tasks such as frequency and temporal discrimination. Many of these children also exhibit abnormal encoding of speech stimuli in the auditory brainstem, even though responses to click stimuli are normal. In typically developing children the auditory brainstem response reflects acoustic differences between contrastive stop consonants. The current study investigated whether this subcortical differentiation of stop consonants was related to reading ability and speech-in-noise performance. Across a group of children with a wide range of reading ability, the subcortical differentiation of 3 speech stimuli ([ba], [da], [ga]) was found to be correlated with phonological awareness, reading, and speech-in-noise perception, with better performers exhibiting greater differences among responses to the 3 syllables. When subjects were categorized into terciles based on phonological awareness and speech-in-noise performance, the top-performing third in each grouping had greater subcortical differentiation than the bottom third. These results are consistent with the view that the neural processes underlying phonological awareness and speech-in-noise perception depend on reciprocal interactions between cognitive and perceptual processes.